Biological management of powdery mildew of grapes - S.V. KOLASE, K.S. RAGHUWANSHI*, M.V. TEKALE and (Indian Phytopathology, 2016)
Powdery mildew caused by Uncinula necator is an economically important disease of grapes in the world. Injudicious use of pesticides have created major hurdle in export of grapes hence the study was carried out to reduce the pesticide use and thereby residues and also find out eco-friendly solution to mitigate the disease with the help of biological antagonist such as yeast. The twenty two yeast isolates were obtained from leaf samples collected from different districts of Maharashtra State and evaluated against Uncinula necator under field condition. Out of twenty two isolates, the isolates MPKVYI-12, MPKVYI-14, ANYI-1, ANYI-2, ANYI-3, SATYI-1, SOLYI-1 and NYI-1 were found effective, where intensity of the fungus reduced upto 50 per cent. In subsequent test the isolates ANYI-2, SATYI-1 and NYI-1 were reduced the disease intensity upto 80 per cent and out of these three, the isolate no 22 (NYI-1) was found most effective. In the mechanism of phyto parasitism it was observed that the spores of yeast get attached to the epidermis of fungal spore and which further get disturbed and shrinked. In physiological studies of eight yeast isolates, it was observed that the growth of all isolates were excellent at temperature 20-35Â°C and 8-10 pH. In pesticide compatibility study all the eight yeast isolates were found compatible with commonly used fungicides and antibiotics. The grape vine leaf microflora was altered due to spray of yeast.